Cluster Preface: Organic Photoredox Catalysis in Synthesis – Honoring Professor Shunichi Fukuzumi’s 70th Birthday - Nicewicz, David (Synlett, 2022)
Dave Nicewicz was born and raised in the United States in Central New Jersey, before moving to North Carolina, where he completed his Bachelor’s (2000) and Master’s (2001) degrees in Chemistry at the University of North Carolina (USA) at Charlotte with Professor Craig A. Ogle. He then moved to the University of North Carolina at Chapel Hill (USA) where he completed his Ph.D. with Professor Jeffrey S. Johnson. Dave’s studies were focused on the development of acyl anion equivalents generated via 1,2-Brook rearrangements from silylglyoxylates, which he was able to successfully apply to a total synthesis of zaragozic acid C to complete his Ph.D. in 2006. Following his graduate education, Nicewicz moved back to his native New Jersey in 2007, where he was a Ruth L. Kirschstein Postdoctoral Fellow in the laboratories of Professor David W. C. MacMillan. It was during this time that Nicewicz pioneered the use of ruthenium photoredox catalysis in combination with chiral amine organocatalysis to develop a general method for enantioselective aldehyde alkylation. In July of 2009, Dave went on to begin his independent career at the University of North Carolina at Chapel Hill, where his laboratory has focused on organic photoredox catalysis for the development of novel chemical reactivity. He has received a number of awards early on in his career from the University of North Carolina (James Moeser Award for Distinguished Research; Ruth Hettleman Prize for Artistic and Scholarly Achievement), industry (Boehringer Ingelheim New Investigator Award in Organic Chemistry; Amgen Young Investigator Award; Eli Lilly Grantee Award), private foundations (Packard Fellowship in Science and Engineering; Camille Prof. D. A. Nicewicz Dreyfus Teacher-Scholar Award) as well as international recognition (Society of Synthetic Organic Chemistry, Japan Lectureship Award; The 13th Hirata Award, Nagoya University). In 2015, he was promoted to the rank of Associate Professor, where he leads a research group focused on organic methodology development, catalysis and complex molecule synthesis